2019
DOI: 10.1115/1.4043789
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Ionization for Detection of Misfire, Knock, and Sporadic Preignition in a Gasoline Direct Injection Engine

Abstract: Detection of combustion-related phenomena such as misfire, knock, and sporadic preignition is very important for the development of electronic controls needed for the gasoline direct injection engines to meet the production goals in power, fuel economy, and low emissions. This paper applies several types of combustion ionization sensors, and a pressure transducer that directly senses the in-cylinder combustion, and the knock sensor which is an accelerometer that detects the impact of combustion on engine struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Tong et al 30 revealed that by detecting the abnormal increase in the ion-current signal before the spark-ignition signal, pre-ignition events can be detected as precisely as with the cylinder-pressure signal. Ayad et al 31 investigated three types of ion-current sensors: stand-alone ion probe, spark-plug type, and fuel-injector type, and succeeded in detecting the pre-ignition cycle by identifying the combustion start timing with all three types of ion-current sensors. On the basis of above prior research, it was proved that pre-ignition affects the timing at which the ion-current signal is generated.…”
Section: Introductionmentioning
confidence: 99%
“…Tong et al 30 revealed that by detecting the abnormal increase in the ion-current signal before the spark-ignition signal, pre-ignition events can be detected as precisely as with the cylinder-pressure signal. Ayad et al 31 investigated three types of ion-current sensors: stand-alone ion probe, spark-plug type, and fuel-injector type, and succeeded in detecting the pre-ignition cycle by identifying the combustion start timing with all three types of ion-current sensors. On the basis of above prior research, it was proved that pre-ignition affects the timing at which the ion-current signal is generated.…”
Section: Introductionmentioning
confidence: 99%
“…Knocking phenomenon causes a high-frequency component in the ion-current signal, and that component can be used as an indicator of knocking intensity. Giglio et al (2009) showed that the oscillation of ion-current correlates with pressure oscillation induced by knocking, and Ayad et al (2019) compared the different types of ion-current sensors including a sparkplug type and a stand-alone type and concluded all of them could be applicable for knocking detection. Kinoshita et al (2000) concluded that the oscillation is caused by the change in ion density with a pressure wave, and the oscillation frequency depends on the polar character of the ion probe.…”
Section: Introductionmentioning
confidence: 99%